Dust-induced radiative feedbacks in north China: A dust storm episode modeling study using WRF-Chem. (March 2016) - Liu, Lixia; Huang, Xin; Ding, Aijun; Fu, Congbin
Abstract: Radiative forcing of dust aerosol and the radiative feedbacks on the planetary boundary layer (PBL) in North China during a typical Asian dust storm in the early April of 2011 was investigated by an online coupled meteorology-chemistry-aerosol model WRF-Chem. Dust-induced daily mean radiative forcing (RF) at the ground surface and in the atmosphere were estimated to be −21.1 W m −2 and 12.7 W m −2, respectively, over Gobi desert, and −13.1 W m −2 and 4.8 W m −2, respectively, in downwind region over the North China Plain (NCP). Comparatively, radiative perturbation on short-wave radiation was approximately twice that on long-wave radiation in magnitude. In the daytime, when solar radiation dominated, the surface cooling and atmospheric heating due to dust increased PBL stability, leading to reductions of PBL height (PBLH) about 90 m and decreases in wind speed up to 0.4 m s −1 . On the contrary, the radiative forcing in terrestrial radiation caused an opposite response at night, especially in the downwind region. Although dust emission was repressed by weakened wind speed during daytime, the elevated PBLH along with larger deflation at night lifted more dust particles to higher altitude (by up to 75 m in average), which prolonged dust residence time in the atmosphere and further intensified dust loading in downwind areas. Taking dust radiative feedbacks into consideration notably narrowed gaps between model-predicted air temperature vertical profiles with corresponding observations, suggesting a significant importance of dust-radiation interaction in PBL meteorology during dust storms. Highlights: Radiative behaviors of dust differ in source regions and downwind areas. Dust stabilizes daytime PBL whereas it poses an opposite effect at night. Enhanced nighttime convection promoted the long-range transport of dust.